Place-Based Collaborative Action as a Means of Delivering Goods and Services in Rural Areas of Developed Economies - Bill Slee; Jonathan Hopkins (World)
This paper challenges the simplified binary division of suppliers of goods and services into market or state categories and identifies the continued relevance of household, community, and third-sector provision in rural areas. We explain the emergence, survival, and development of place-based and collaborative action using a three-fold typology, reflecting differences in the motivations and rationales for providing goods and services in these ways. In a place-based context, some communities have acted collectively using collaborative agency. Many observers of rural community development have suggested that place-based communitarian action may be unable to break free from class-based controls, but this is contested by some compelling examples. Where supported by effective public policy, place-based communitarianism can offer an alternative mode of provision for a wide range of services. Using Scotland as an example, this paper explores the dynamics of interactions between community and policy actors in land acquisition and management, renewable energy, and social care.